Keringanan Dalam Hukum Islam - Siregar, Syapar Alim (IAIN Padangsidimpuan, 2019)
Do Muslims have relief in implementing Islamic law? answer, he, that is rukhshah. Rukhsah is the religiousness given by the Shari'a to a Muslim who fulfills his terms and conditions. For example, when a person on a trip he is entitled to the reliefs that have been given by Shara ', including praying or calling' prayers, breaking the fast during the day of Ramadan, sweeping khuf for three days, performing sunnah prayers on a vehicle, leaving Friday prayers 'at, eat the carcass when it is in dharurat.Â